Analysis of The Use of Digital Learning Media Before and After Pandemic - Siregar, Sri Utami Kholilla Mora; Kasmawati (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2022)
The purpose of this study was to see the extent of student interest in participating in learning before the pandemic through the application of monotonous conventional methods with learning using digital media after the pandemic. The type of research used in this study is a qualitative research type, for processing data obtained based on observations and publishing a questionnaire that will be answered by all 2018 physics students. In this case, the researcher observes student activities during learning and evaluates them at the end of each lesson. The use of digital learning media for physics students is obtained from research on student answers through questionnaires that can be uploaded via the given page. It is known that 70% of students prefer learning using digital media after the pandemic compared to before the pandemic. The results of this study were obtained by observing an increase in student interest in learning by using digital learning media in the subject of study and learning of physics students for the 2018 class of the teaching faculty of UGN Padangsidimpuan.